Anxiolytic and sedative effects of extracts and essential oil from Citrus aurantium L. - Carvalho-Freitas, MIR; Costa, M. (Pharmaceutical Soc Japan, 2002)
Citrus aurantium L. is commonly used as an alternative treatment for insomnia, anxiety and epilepsy. Essential oil from peel (EOP) and hydroethanolic (70% w/v) extract (HE) from leaves were obtained. Hexanic (HF), dichloromethanic (DF) and final aqueous (AF) fractions were obtained from HE by successive partitions. Swiss male mice (35-45 g) were treated orally with 0.5 or 1.0 g/kg of these preparations 30 min before the experiments for the evaluation of the sedative/hypnotic activity (sleeping time induced by sodium pentobarbital-SPB: 40 mg/kg, i.p.), anxiolytic activity (elevated plus maze-EPM) and anticonvulsant activity (induced by pentylenetetrazole-PTZ: 85 mg/kg, se or by maximal electroshock-MES: 50 mA, 0.11s, corneal). The results showed that EOP (0.5 g/kg) increased the latency period of tonic seizures in both convulsing experimental models. This effect was not dose-dependent. Treatment with 1.0 g/kg increased the sleeping time induced by barbiturates and the time spent in the open arms of the EPM. Specific tests indicated that the preparation, in both doses used, did not promote deficits in general activity or motor coordination. HF and DF fractions (1.0 g/kg) did not interfere in the epileptic seizures, but were able to enhance the sleeping time induced by barbiturates. The results obtained with EOP in the anxiety model, and with EOP, HF and DF in the sedation model, are in accord with the ethnopharmacological use of Citrus aurantium L., which could be useful in primary medical care, after toxicological investigation.
Keywords: anxiolytic; sedative; anticonvulsant; Citrus aurantium L.; essential oil; mice